Assessing the Translation of English Janus Words into Arabic - Essam Taher Muhammed Essam Taher Muhammed (مجلة النور للدراسات الانسانية)
The aim of this study is to highlight the challenges that might arise while translating English Janus words into Arabic. It is hypothesized that the clues provided by the linguistic context, which inexperienced translators often fail to account for, have a major impact on how the English Janus words are rendered. In addition, the study assumes that freshman translators tend to automatically give a single meaning to each lexical item, without taking into consideration the several additional or secondary meanings that a lexical item might have. To accomplish the aims of the present study, the researcher selects five examples of English Janus words taken from Mittendorff, A. (2018). To collect data for this study, the chosen samples are presented to six MA students at Mosul University's Department of Translation to translate into Arabic during the academic year 2023–2024. © THIS IS AN OPEN ACCESS ARTICLE UNDER THE CC BY LICENSE. http://creativecommons.org/licenses/by/4.0/ The study concludes that the respondents, in several cases, fail to take into account the clues provided by the linguistic context, ultimately resulting in several inaccurate renditions. Following that, the researcher strongly suggests that the influence of the linguistic context should be taken into consideration while translating such challenging terms.